Neoadjuvant chemotherapy and primary‐first approach for rectal cancer with synchronous liver metastases. (June 2014) - Gall, T. M. H.; Basyouny, M.; Frampton, A. E.; Darzi, A.; Ziprin, P.; Dawson, P.; Paraskeva, P.; Habib, N. A.; Spalding, D. R. C.; Cleator, S.; Lowdell, C.; Jiao, L. R.
Abstract Aim Up to a quarter of patients with rectal cancer have synchronous liver metastases at the time of diagnosis. This is a predictor of poor outcome. There are no standardized guidelines for treatment. We reviewed the outcomes of our patients with synchronous rectal liver metastases treated with a curative intent by neoadjuvant chemotherapy with or without chemoradiotherapy followed by resection of the primary tumour and then liver metastases. Method Between 2004 and 2012, patients who presented with rectal cancer and synchronous liver metastasis were treated with curative intent with peri‐operative systemic chemotherapy as the first line of treatment. Responders to chemotherapy underwent resection of the primary tumour with or without preoperative chemoradiotherapy followed by hepatic resection. Results Fifty‐three rectal cancer patients with 152 synchronous liver lesions were identified. After a median follow‐up of 29.6 months, the median survival was 41.4 months. Overall survival was 59.0% at 3 years and 39.0% at 5 years. Conclusion Rectal resection before hepatic resection combined with neoadjuvant chemotherapy is associated with promising clinical outcome. It allows downstaging of liver lesions and removal of the primary tumour before the progression of further micrometastases. Furthermore, patients who do not respond to chemotherapy can be identified and may avoid major surgical intervention.